Tecnologia educacional para pessoas com diabetes mellitus: práticas de promoção da saúde durante e após o cenário de Covid-19 - Santos, Carla Lidiane Jácome dos (2023)
Introduction: Infection with the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus, which caused the disease coronavirus-19 (COVID-19), mainly affected vulnerable groups with a higher risk of mortality, among which is the Diabetes Mellitus. One way to promote health promotion actions for people with DM during and after-COVID-19 is through the use of educational technologies, such as educational booklets. Objective: to analyze the validation evidence of an educational technology promoting the health of people with Diabetes Mellitus in the scenario during and after COVID-19. Method: methodological, multicenter study of construction and validation of content and appearance by specialists and by the person with diabetes, developed in three stages: an integrative literature review was carried out to support the elaboration of the technology; the validation of content and appearance by the specialists took place, finally, the validation of the content and appearance by the person with diabetes. Data analysis in the first stage was carried out by two independent researchers, in the second stage the Content Validity Ratio was used and in the third stage the Content Validity Index. The research project was approved by the Ethics and Research Committee of the University Hospital Alcides Carneiro of the Federal University of Campina Grande, opinion nº 4.329.230/2021. Results: In the first stage, the sample consisted of 17 articles categorized into individual, collective and governmental measures; in the second stage, 27 specialists from the most varied regions of Brazil participated in the evaluation of the educational booklet, reaching adequate Content Validity Ratio indices for content and appearance validation, in the third stage, 87 people with diabetes evaluated the booklet in terms of content and appearance. appearance achieving Content Validity Index > 0.95. Final considerations: The booklet responds to the proposed objective by presenting itself as accurate and valid. It is expected that it will actually be used to promote the health of people with diabetes, since it constitutes an instrument validated by diabetes specialists and with the target audience.